Pathogenicity of Misfolded and Dimeric HLA-B27 Molecules - Antoniou, Antony N. (Hindawi Publishing Corporation, 2011)
The association between HLA-B27 and the group of autoimmune inflammatory arthritic diseases, the spondyloarthropathies (SpAs) which include ankylosing spondylitis (AS) and Reactive Arthritis (ReA), has been well established and remains the strongest association between any HLA molecule and autoimmune disease. The mechanism behind this striking association remains elusive; however animal model and biochemical data suggest that HLA-B27 misfolding may be key to understanding its association with the SpAs. Recent investigations have focused on the unusual biochemical structures of HLA-B27 and their potential role in SpA pathogenesis. Here we discuss how these unusual biochemical structures may participate in cellular events leading to chronic inflammation and thus disease progression.